2018
DOI: 10.2298/pac1802111z
|View full text |Cite
|
Sign up to set email alerts
|

Dilatrometric sintering study and characterization of alumina-nickel composites

Abstract: Alumina-nickel composite samples (with 0, 10 and 20 vol.% of Ni) are prepared via slip casting method. Nickel and aluminium oxide powders were used as precursors and diammonium hydrocitrate and citric acid were used as dispersants. The obtained materials were analysed by dilatometry, X-ray diffraction and SEM. The densities were measured by Archimedes method and the hardness and fracture toughness were determined by using Vickers hardness tester. Special attention was paid to the linear shrinkage and the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…4c). This could be a consequence of hard agglomerates presented in the activated AC-60 sample, which was also previously reported [29].…”
Section: Resultssupporting
confidence: 82%
“…4c). This could be a consequence of hard agglomerates presented in the activated AC-60 sample, which was also previously reported [29].…”
Section: Resultssupporting
confidence: 82%
“…The result of the hardness measurements showed that composites from Series I (Al 2 O 3 + 10 vol% metallic phase) were characterized by the hardness value equal to 5.52 ± 0.56 GPa, whereas the hardness of the Series II (Al 2 O 3 + 15 vol% metallic phase) composites was 4.88 ± 0.84 GPa. Compared to the hardness of samples created from pure alumina TM-DAR [26] obtained, the result is lower ca. 11 GPa.…”
Section: Methodsmentioning
confidence: 75%
“…Figure 6 presents the dilatometer curves for pellets with 5 wt.%, 10 wt.%, 15 wt.%, and 20 wt.% BBSZ glass containing pellets along with the temperature differential of DL/L 0 , where L 0 is the original length, and DL is change in length. 31 The lowering of sintering temperature with increasing glass content indicates liquid-phase sintering. Evidence of liquid-phase sintering assisting in the reduction in sintering temperature has also been presented by Kim et al for the sintering of BaTi 4 O 9 pellets using zinc borate glass.…”
Section: Methodsmentioning
confidence: 99%